Impact of schistosome infection on Plasmodium falciparum Malariometric indices and immune correlates in school age children in Burma Valley, Zimbabwe. - Davison T Sangweme; Nicholas Midzi; Sekesai Zinyowera-Mutapuri; Takafira Mduluza; Marie Diener-West; Nirbhay Kumar (Public Library of Science (PLoS), 2010)
A group of children aged 6-17 years was recruited and followed up for 12 months to study the impact of schistosome infection on malaria parasite prevalence, density, distribution and anemia. Levels of cytokines, malaria specific antibodies in plasma and parasite growth inhibition capacities were assessed. Baseline results suggested an increased prevalence of malaria parasites in children co-infected with schistosomiasis (31%) compared to children infected with malaria only (25%) (p = 0.064). Moreover, children co-infected with schistosomes and malaria had higher sexual stage geometric mean malaria parasite density (189 gametocytes/µl) than children infected with malaria only (73/µl gametocytes) (p = 0.043). In addition, a larger percentage of co-infected children (57%) had gametocytes as observed by microscopy compared to the malaria only infected children (36%) (p = 0.06). There was no difference between the two groups in terms of the prevalence of anemia, which was approximately 64% in both groups (p = 0.9). Plasma from malaria-infected children exhibited higher malaria antibody activity compared to the controls (p = 0.001) but was not different between malaria and schistosome plus malaria infected groups (p = 0.44) and malaria parasite growth inhibition activity at baseline was higher in the malaria-only infected group of children than in the co-infected group though not reaching statistical significance (p = 0.5). Higher prevalence and higher mean gametocyte density in the peripheral blood may have implications in malaria transmission dynamics during co-infection with helminths.